Sports Chaplaincy, Theology and Social Theory Disrupting Performance-Based Identity in Elite Sporting Contexts - Luke Jones; Andrew Parker; Graham Daniels (Religions, 2020)
Existing literature on the work of sports chaplains has focused primarily on practitioner accounts of chaplaincy with elite athletes. While these narratives provide useful descriptions of personal experience and practical application, they are largely devoid of theoretical grounding. This paper seeks to address this imbalance by proposing the need for sports chaplains to have a more critical understanding of sport and its relational dynamics. We begin by problematizing some of the historical assumptions underpinning elite sport, especially in relation to identity formation. We then explore some of the moral dilemmas which may be experienced by Christian athletes who inhabit contemporary sporting contexts. In line with the work of established sociological scholars, we then move to a critical analysis of performance-based identity and how an understanding of sociological concepts and ideas might assist chaplains in their work with elite athletes. The paper concludes by identifying sports chaplains as key figures in the disruption of performance-based identity.